Reconstruction of The Selodang Mayang Dance at Amantubillah Palace in Mempawah, West Kalimantan Province - Deki Prasetya Ardiansyah; Slamet Slamet; Aris Setiawan (Jurnal Seni Tari, 2023)
This article is the result of research that focuses on the main issue of how the process of reconstructing the Selodang Mayang dance at Amantubillah Palace takes place. The Selodang Mayang dance is a welcoming dance that developed within the Royal Palace of Amantubillah in Mempawah Regency, West Kalimantan Province. The aim of this research was to understand and explain each stage of the reconstruction process of the Selodang Mayang dance, which aimed to revive the Selodang Mayang dance. The forms of the reconstructed Selodang Mayang dance include 1) Movement, 2) Music, 3) Costumes and Makeup, 4) Props, and 5) Floor Patterns. This research employed a qualitative method with an interaction analysis approach. The results of this research revealed a series of movements of the Selodang Mayang dance that use basic graceful steps of lenggang, with arms waving left and right in accordance with the rhythm of the accompanying music. In these movements, there are absolute rules from the palace regarding the motifs of the Selodang Mayang dance, such as graceful steps, arms not lifted beyond 45 degrees, a smiling face, no spinning movements, not turning the back to guests, keeping the legs from spreading wide, and adapting the movements to the lyrics used in the accompanying Selodang Mayang dance. The research findings also include the process conducted by the Selodang Mayang dance reconstruction team in the effort to preserve classical dance art. The objective of this research was to understand, study, and preserve the cultural values existing in Mempawah Regency, so that the Selodang Mayang dance continues to exist and thrive within the palace and the local community.